2020
DOI: 10.3390/app10238698
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Osteoarthritic Effects of Terminalia Chebula Fruit Extract (AyuFlex®) in Interleukin-1β-Induced Human Chondrocytes and in Rat Models of Monosodium Iodoacetate (MIA)-Induced Osteoarthritis

Abstract: Osteoarthritis (OA) is a general joint illness caused by the destruction of joint cartilage, and is common in the population of old people. Its occurrence is related to inflammatory reactions and cartilage degradation. AyuFlex® is an aqueous extract of Terminalia chebula fruit, and T. chebula has been utilized extensively in several traditional oriental medications for the management of diverse diseases. Pre-clinical and clinical research has shown its antioxidant and anti-inflammatory effectiveness. Neverthel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…Several researchers have used this model and performed mechanistic studies to approve functional health materials. For example, AyuFlex ® , an extract from Terminalia chebula Retzins, is effective in the treatment of MIA-induced OA through significant inhibition of OA symptoms such as oxidative stress, cartilage damage, and changes in cytokine and MMP regulation in arthrodial cartilage [33]. Additionally, Andrographis paniculate extracts were approved for the treatment of joint health in an MIA-induced OA model by decreasing the levels of inflammatory cytokines, namely, IL-1β, IL-6, and TNF-α, and the joint tissue degradation enzyme, MMP [34].…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have used this model and performed mechanistic studies to approve functional health materials. For example, AyuFlex ® , an extract from Terminalia chebula Retzins, is effective in the treatment of MIA-induced OA through significant inhibition of OA symptoms such as oxidative stress, cartilage damage, and changes in cytokine and MMP regulation in arthrodial cartilage [33]. Additionally, Andrographis paniculate extracts were approved for the treatment of joint health in an MIA-induced OA model by decreasing the levels of inflammatory cytokines, namely, IL-1β, IL-6, and TNF-α, and the joint tissue degradation enzyme, MMP [34].…”
Section: Discussionmentioning
confidence: 99%
“…Fruits of Terminalia chebula are used as crude drugs in many traditional medicine systems around the world due to potent antioxidant, hepatoprotective and anti-diabetic activities [14]. Kim et al [15] reported the anti-osteoarthritic activity of aqueous extracts of Terminalia chebula fruit in interleukin-1β-induced human chondrocytes and monosodium iodoacetate-induced osteoarthritis in model rats.…”
mentioning
confidence: 99%